Análise das demonstrações financeiras das empresas do ramo petrolífero listadas na BM&FBovespa: uma abordagem após a convergência contábil - Kottwitz, Joones Vanderlei (2011)
There are countless benefits of accounting convergence. Among them are: participation and easier access to capital markets globalized, reducing borrowing costs and financing, for better comparability of accounting information, the greater confidence of foreign investors and transparency and credibility of the financial market. This work made use of a sample of four companies in the oil business, listed on the Stock Exchange of São Paulo / SP, belonging to the BM&FBOVESPA. For this survey, information was sought on the financial statements published in the period 2005 to 2010. Taken individually these annual reports, we sought to identify changes caused by the international accounting standards regarding the recognition of liabilities and equity, which influence the capital structure of the companies concerned. It was concluded therefore that most companies just use the new recommendations in their statements, some claim these changes only in the notes in 2010.